EVALUASI RUMUSAN KEBIJAKAN PUBLIK - Dikson Silitonga (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2017)
In general, this research is aimed at evaluating to what extent the effectiveness of implementation of National Exam policy in mapping and increasing the quality of primary education in Indonesia. By using the Stake’s Countenance evaluation model, this research uses a qualitative and descriptive statistic (simple quantitative) approach with the techniques of data collection through a library study as secondary data sources, deep interviews and observation as primary data sources. On the antecedents phase, the evaluation results show that the conduction of national exam is based on the empirical reason and with a clear legal basis hierarchically, a proper formulation process as well having a clarity of content.